Health Care Professionals' Experiences of Web-Based Symptom Checkers for Triage: Cross-sectional Survey Study - Sari Kujala; Iiris Hörhammer (JMIR Publications, 2022)
BackgroundWeb-based symptom checkers are promising tools that provide help to patients seeking guidance on health problems. Many health organizations have started using them to enhance triage. Patients use the symptom checker to report their symptoms online and submit the report to the health care center through the system. Health care professionals (registered nurse, practical nurse, general physician, physiotherapist, etc) receive patient inquiries with urgency rating, decide on actions to be taken, and communicate these to the patients. The success of the adoption, however, depends on whether the tools can efficiently support health care professionals' workflow and achieve their support. ObjectiveThis study explores the factors influencing health care professionals' support for a web-based symptom checker for triage. MethodsData were collected through a web-based survey of 639 health care professionals using either of the two most used web-based symptom checkers in the Finnish public primary care. Linear regression models were fitted to study the associations between the study variables and health care professionals' support for the symptom checkers. In addition, the health care professionals' comments collected via survey were qualitatively analyzed to elicit additional insights about the benefits and challenges of the clinical use of symptom checkers. ResultsResults show that the perceived beneficial influence of the symptom checkers on health care professionals' work and the perceived usability of the tools were positively associated with professionals' support. The perceived benefits to patients and organizational support for use were positively associated, and threat to professionals' autonomy was negatively associated with health care professionals' support. These associations were, however, not independent of other factors included in the models. The influences on professionals' work were both positive and negative; the tools streamlined work by providing preliminary information on patients and reduced the number of phone calls, but they also created extra work as the professionals needed to call patients and ask clarifying questions. Managing time between the use of symptom checkers and other tasks was also challenging. Meanwhile, according to health care professionals' experience, the symptom checkers benefited patients as they received help quickly with a lower threshold for care. ConclusionsThe efficient use of symptom checkers for triage requires usable solutions that support health care professionals' work. High-quality information about the patients' conditions and an efficient way of communicating with patients are needed. Using a new eHealth tool also requires that health organizations and teams reorganize their workflows and work distributions to support clinical processes.